Optimizing the Role of Urban Open Space in Supporting the Increasing of Public Awareness and Compliance with Health Protocols during the Pandemic (International Journal of Built Environment and Sustainability, 2022)
The level of the spread of covid-19, which is still high in the city of Semarang, indicates the low level of public awareness in complying with health protocols. The role of urban open space in Semarang City needs to be optimized to support this effort by adding several facilities that did not exist before the pandemic, so that people comply with health protocols, wear masks, wash their hands frequently and maintain physical distance when carrying out their social activities. The aim of this study is to determine how to optimize the role of public open space in supporting efforts to maintain the health of urban communities based on public awareness in complying with health protocols when doing activities. The research was conducted in three open spaces in Semarang, Indonesia, using survey methods and a descriptive qualitative analysis by observing the physical condition of the park, the behavior of the people in doing their activities, and park management officers. The results show that the three locations are now equipped with supporting facilities, but they are less effective in forcing people to remain obedient when doing activities. The level of public awareness and compliance has not met expectations and most of the people are still ignorant. Therefore, there is still a need to add more attractive and more massive facilities and to give more socialisations so that urban open spaces can be safe and healthy locations to visit as well as to play a more optimal role in improving people's physical and mental health during the pandemic
Keywords: Urban open space; health protocols; public awareness and compliance; pandemic